PODCAST SUARA PUAN SEBAGAI SARANA LITERASI DIGITAL KAUM PEREMPUAN MELALUI PLATFORM SPOTIFY - Maria Juli Insani Simbolon; Besti Rohana Simbolon (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This research is entitled " Podcast Suara Puan Sebagai Sarana Literasi Digital Kaum Perempuan Melalui Platform Spotify ". In human life in various periods and periods, there will be different developments. Human development will make humans learn and observe more and more in their development. Many things can happen in human life. Including in the current pandemic era, humans have become more creative in communicating. One of the human efforts to be able to keep running one of the digital technologies that is rising and becoming a new trend during the pandemic is podcasts. Podcasts or broadcasts are a new form of entertainment in the form of audio formats and later can also be enjoyed in audiovisual form. A Podcast is recording. It contains conversations ranging from half an hour to an hour, covering interesting and specific topics. Usually podcasts are delivered in monologue, dialogue or in groups (multi-hosted podcasts). The method of implementing the research approach is through literature study, in-depth interviews and analyzing it using descriptive analysis techniques. From the results of the study, it was found that the Suara Puan podcast is one of the answers at the same time as new communication channels offered by various media to get information about women.